2019
DOI: 10.3390/fi11090190
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning-Based Sentimental Analysis for Large-Scale Imbalanced Twitter Data

Abstract: Emotions detection in social media is very effective to measure the mood of people about a specific topic, news, or product. It has a wide range of applications, including identifying psychological conditions such as anxiety or depression in users. However, it is a challenging task to distinguish useful emotions’ features from a large corpus of text because emotions are subjective, with limited fuzzy boundaries that may be expressed in different terminologies and perceptions. To tackle this issue, this paper p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In our future work, we plan to refine our results by expanding the data set. We also intend to further explore this topic, particularly in terms of detecting and characterizing spam content, methods, and campaigns (as opposed to spamming accounts) [38]. In addition, we will try to distinguish translated tweets created by an Arab writer [39].…”
Section: Discussionmentioning
confidence: 99%
“…In our future work, we plan to refine our results by expanding the data set. We also intend to further explore this topic, particularly in terms of detecting and characterizing spam content, methods, and campaigns (as opposed to spamming accounts) [38]. In addition, we will try to distinguish translated tweets created by an Arab writer [39].…”
Section: Discussionmentioning
confidence: 99%
“…The disadvantage was that, although the users were correctly classified, detecting them as stressed required an excessive amount of time. So, the challenge here is to reduce the depression detection time. More machine learning or deep learning systems 86 that are less likely to over fit the data should be used, as well as a more accurate way to measure the impact of features, should be found. As per the survey, it has been found that most of the developed models only recognize tweets in the English language 87 . So a more reliable system can be developed to consider tweets written in other languages.…”
Section: Challenges and Future Directionmentioning
confidence: 99%
“…3. More machine learning or deep learning systems 86 that are less likely to over fit the data should be used, as well as a more accurate way to measure the impact of features, should be found. As per the survey, it has been found that most of the developed models only recognize tweets in the English language.…”
Section: Depression Detection From Social Postmentioning
confidence: 99%
“…Human languages can be analyzed and understood by NLP algorithms. Sentiment analysis intends to parse sentiment from textual information and extract their polarity and viewpoint [26]. Singla et al [27] proposed a method to analyze the Amazon mobile phone reviews, which are categorized into negative and positive polarity.…”
Section: Text Analysismentioning
confidence: 99%